Characterization of acute pain‐induced behavioral passivity in mice: Insights from statistical modeling. (18th March 2021) - Yeung, Sung Ching; Ganesan, Kumar; Wong, Stanley Sau Ching; Chung, Sookja K.; Cheung, Chi Wai
Abstract: Affective‐motivational disturbances are highly inconsistent in animal pain models. The reproducibility of the open‐field test in assessing anxiety, malaise or disability remains controversial despite its popularity. While traumatic, persistent or multiregional pain models are commonly considered more effective in inducing negative affect or functional impairment, the early psychobehavioral changes before pain chronification are often underexplored. Here, we aimed to clarify the fundamental relationship between hypernociception and passive distress‐like behavior using a model of transient inflammatory pain. To minimize latent confounders and increase data consistency, male C57BL/6N mice were habituated to the open‐field arena 6 times before receiving the unilateral intraplantar injection of prostaglandin E2 (PGE2) or vehicle. Open‐field (40‐min exploration) and nociceptive behavior were evaluated repeatedly along the course of hypernociception in both wild‐type and transgenic mice with a known pronociceptive phenotype. To reduce subjectivity, multivariate open‐field behavioral outcomes were analyzed by statistical modeling based on exploratory factor analyses, which yielded a 2‐factor solution. Within 3 hr after PGE2 injection, mice developed significantly reduced center exploration (factor 1) and a marginally significant increase in their habituation tendency (factor 2), which were not apparent in vehicle‐injected mice. The behavioral passivity generally improved as hypernociception subsided. Therefore, transient inflammatory irritation is sufficient to suppress mouse open‐field exploratory activity. The apparent absence of late affective‐motivational changes in some rodents with prolonged hypernociception may not imply a lack of preceding or underlying neuropsychological alterations. Procedural pain after invasive animal experiments, however small, should be assessed and adequately controlled as a potential research confounder. Abstract : Pain‐depressed behaviors are valuable translational research outcomes. After allowing adequate pre‐test habituation, our longitudinal open‐field assay protocol and statistical modeling analyses have characterized the rapid emergence of behavioral passivity in male mice under transient inflammatory pain. Our study encourages researchers to assess the latent influence of acute procedural pain on neurobehavioral outcomes after invasive experiments.